Development of a Web-Based Self-Health Screening Kiosk for The Participants of Chronic Disease Management Program (PROLANIS) - Setya Wijayanta; Eliyah Eliyah; Asharul Fahyudi; Sylvia Anjani; Oki Setiono (P3M Politeknik Negeri Jember, 2026)
Current PROLANIS screening workflows at primary healthcare facilities remain predominantly manual and complex, characterized by lengthy registration processes, laboratory examinations, medical consultations, therapeutic exercises, health education sessions, and pharmacy visits. These inefficiencies result in prolonged patient queues, duplicate documentation, delayed data aggregation, and excessive workload for healthcare personnel, ultimately compromising program effectiveness and participant satisfaction. This study addresses these challenges through the development of a web-based self-health screening kiosk utilizing a Research and Development (R&D) approach with a prototyping model. System evaluation focused specifically on user interface/experience (UI/UX) feasibility, rather than clinical effectiveness, involving six PROLANIS officers from Sidorejo Lor and Sidorejo Kidul Community Health Centers using a structured assessment instrument. Results yielded an average score of 4.0 (out of 5), indicating good design consistency, responsiveness, and functionality, though improvements remain necessary in ease of use and visual layout. The prototype demonstrates potential to enhance PROLANIS efficiency but requires broader clinical validation and system integration testing.